Relevance of Glucagon-Like Peptide 1 (GLP-1) in Inflammatory Bowel Diseases: A Narrative Review - Antonietta Gerarda Gravina; Raffaele Pellegrino; Michele Izzo; Ilaria De Costanzo; Giuseppe Imperio; Fabio Landa; Assunta Tambaro; Alessandro Federico (Current Issues in Molecular Biology)
Inflammatory bowel diseases (IBDs) are complex immune-mediated disorders characterised by an unpredictable direction and commonly associated metabolic comorbidities along with obesity and type 2 diabetes mellitus (T2DM). Recent evidence has highlighted the therapeutic capacity of glucagon-like peptide 1 receptor agonists (GLP-1 RAs), already employed in treating T2DM and obesity, in modulating systemic and intestinal inflammatory responses. This narrative review examines the general organic traits of GLP-1, with a specific awareness of its primary gastrointestinal actions and the efficacy of GLP-1 RAs in promoting weight loss and dealing with glycaemic control, mainly in sufferers with IBD. Furthermore, the effects of those agonists on the progression of IBD, their protection profile, their impact on bowel preparation for endoscopic procedures, and their therapeutic capacity, supported through preclinical and early clinical studies, are discussed. GLP-1 RAs appear to lessen the intestinal inflammatory burden by enhancing intestinal epithelial barrier features and modulating the gut microbiota. However, further clinical research will be necessary to verify whether GLP-1 RAs could play a position in IBD treatment.